Becoming a resonant leader : develop your emotional intelligence, renew your relationships, sustain your effectiveness - McKee, Annie, 1955-; Boyatzis, Richard E.; Johnston, Frances, 1964- (Boston, Mass. : Harvard Business School Pub., 2008)
Offers activities designed to help leaders develop their emotional intelligence and sustain resonance in relationships.
Leading for real -- Resonant leadership : an approach that works -- Listening to your wake up calls -- Seeing your dream -- Appreciating your real self -- Becoming a resonant leader -- Igniting resonance : creating effectiveness in teams, organizations and communities.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Leadership -- Psychological aspects; Emotional intelligence; Interorganizational relations; Organizational effectiveness; Teams in the workplace -- Management; Emotional intelligence; Interorganizational relations; Leadership -- Psychological aspects; Organizational effectiveness; Teams in the workplace -- Management; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books